Soft power – definicja, źródła i sposób oddziaływania - Łoś, Robert (Studia Polityczne, 2018)
The issue of understanding the power of modern states has not lost its relevance. This can be seen in the different understanding of power in the world. This is despite changes in the international system and a different view of state power. Due to these changes, in addition to obvious determinants of state power, such as military or economic determinants, those defined by soft power should also be taken into account. While this concept was disseminated by J. Nye, it is not new in the literature on the subject. However, it only gained recognition in the late twentieth century, when attempts were made to interpret the growth of the power of states and of superpowers in particular. Then, state power was evaluated by using the terms: hard and soft power. Soft power has its source in norms, values, culture and foreign policy. These basic sources of power affect other international entities to a large extent due to their attractiveness. This attractiveness is accepted (or not), increasing the importance of the state.